Studi Kompetensi Pedagogik Mahasiswa Calon Guru dalam Merancang Pembelajaran Berparadigma Konstruktivis: Pedagogical Competency Studies of Prospective Techers in Designing Contructivist Paradigma Learning - Adawiyah, Rabiatul; Putrawangsa, Susilahudin (Pedagogia : Jurnal Pendidikan, 2019)
The current research intends to uncover prospective teacher competencies in designing an instructional design (learning activities) that in line with paradigm. It is a qualitative-descriptive study. The data are collected through a learning design test. The data then are to obtain the depiction of the level of the subjects’ proficiency in designing an instructional design that fit with view. The subjects of the study are students at the department of Primary Teacher Education of Mataram State Islamic University. The findings conclude that each subject can design a learning activity that satisfies the component of learning components. However, the level of the subjects’ pedagogical competencies in designing learning activities are far away from ideal competencies that should be mastered by professional teachers in designing learning activities.